Clinical Factors and Postoperative Impact of Bile Leak After Liver Resection - Martin, Allison N.; Narayanan, Sowmya; Turrentine, Florence E.; Bauer, Todd W.; Adams, Reid B.; Stukenborg, George J.; Zaydfudim, Victor M. (Journal of gastrointestinal surgery, 2018)
Background Despite technical advances, bile leak remains a significant complication after hepatectomy. The current study uses a targeted multi-institutional dataset to characterize perioperative factors that are associated with bile leakage after hepatectomy to better understand the impact of bile leak on morbidity and mortality. Methods Adult patients in the 2014–2015 ACS NSQIP targeted hepatectomy dataset were linked to the ACS NSQIP PUF dataset. Bivariable and multivariable regression analyses were used to assess the associations between clinical factors and post-hepatectomy bile leak. Results Of 6859 patients, 530 (7.7%) had a postoperative bile leak. Proportion of bile leaks was significantly greater in patients after major compared to minor hepatectomy (12.6 vs. 5.1%, p < 0.001). The proportion of patients with bile leak was significantly greater in patients after major hepatectomy who had concomitant enterohepatic reconstruction (31.8 vs. 10.1%, p < 0.001). Postoperative mortality was significantly greater in patients with bile leaks (6.0 vs. 1.7%, p < 0.001). After adjusting for significant covariates, bile leak was independently associated with increased risk of postoperative morbidity (OR = 4.55; 95% CI 3.72–5.56; p < 0.001). After adjusting for significant effects of postoperative complications, liver failure, and reoperation (all p<0.001), bile leak was not independently associated with increased risk of postoperative mortality ( p = 0.262). Conclusion Major hepatectomy and enterohepatic biliary reconstruction are associated with significantly greater rates of bile leak after liver resection. Bile leak is independently associated with significant postoperative morbidity. Mitigation of bile leak is critical in reducing morbidity and mortality after liver resection.